Ultra-sensitive surface plasmon resonance sensor integrating MXene (Ti3C2TX) and graphene for advanced carcinoembryonic antigen detection - Ali Khodaie; Hamid Heidarzadeh (Scientific Reports)
Abstract Carcinoembryonic antigen (CEA) is a critical biomarker for diagnosing and monitoring cancers such as liver, colon, and breast cancer. This study presents a highly sensitive surface plasmon resonance (SPR) sensor incorporating 2D materials—graphene and MXene (Ti3C2TX)— in a Kretschmann configuration. The sensor, comprising a BK7 prism, gold (Au), graphene, aluminum oxide (Al₂O₃), and MXene, is optimized for detecting CEA in aqueous solutions with high precision. The performance of the proposed sensor was evaluated using the finite difference time domain (FDTD) numerical method, focusing on key parameters such as sensitivity and figure of merit (FOM). Operating at a wavelength of 633 nm, the sensor achieved an exceptional sensitivity of 163.63 deg/RIU and an FOM of 17.52 RIU⁻¹, marking a significant improvement over previously reported SPR biosensors. Comparative analysis further underscores the superior performance of this design, establishing it as a cutting-edge tool for applications in biosensing, medical diagnostics, food safety, and environmental monitoring. The proposed sensor offers significant potential for real-world applications, including clinical diagnostics for early cancer detection, food safety monitoring, and environmental sensing.